COVID-19 in school settings: webinar aimed at both teachers and educators - Paduano, S.; Marchesi, I.; Frezza, G.; Turchi, S.; Bargellini, A. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In the COVID-19 era, we designed the webinar “COVID-19: instructions for use” with the aim of providing clear and actionable information to school staff about the characteristics of the disease, the preventive measures to adopt and the path for early detection and control of COVID-19 in primary schools of Modena province. Methods. We performed a cross-sectional survey using a 7-item closed-ended satisfaction questionnaire selfadministered to webinar participants among school staff of the Modena Municipality and neighbouring. Results. A total of 103 out of 152 (68%) participants delivered the questionnaires. The participating staff came from 29 schools. Most of respondents (83.5%) were primary school teachers following by kindergarten teachers and educators. The overall webinar assessment index was “very good” for 51% of attendees and “good” for the remaining. Nevertheless, 25.2% highlighted the need to have more time dedicated to the discussion.Conclusions. Our project promotes a virtuous circle between school-family and community; so that the benefits can be sustained and enhanced. This may improve the effectiveness of the preventive measures in terms of transmission of SARS-CoV-2 and other virus.